2012
DOI: 10.1017/s0144686x12001110
|View full text |Cite
|
Sign up to set email alerts
|

More than A to B: the role of free bus travel for the mobility and wellbeing of older citizens in London

Abstract: This study contributes to the literature on mobility and wellbeing at older ages through an empirical exploration of the meanings of free bus travel for older citizens, addressing the meanings this holds for older people in urban settings, which have been under-researched. Taking London as a case study, where older citizens have free access to a relatively extensive public transport network through a Freedom Pass, we explore from a public health perspective the mechanisms that link this travel benefit to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 34 publications
5
73
0
2
Order By: Relevance
“…Uptake of benefits conditional on simply being part of a generation also fostered social recognition, solidifying a sense of a 'generation' that was valued. That benefits such as free travel contribute to the ability of older citizens to demonstrate their belonging, participation, independence and competence in their locality, has been noted in previous studies (Green et al, 2014). Here, we further argue that uptake provided a field entirely congruent with generational habitus.…”
Section: Discussionsupporting
confidence: 82%
“…Uptake of benefits conditional on simply being part of a generation also fostered social recognition, solidifying a sense of a 'generation' that was valued. That benefits such as free travel contribute to the ability of older citizens to demonstrate their belonging, participation, independence and competence in their locality, has been noted in previous studies (Green et al, 2014). Here, we further argue that uptake provided a field entirely congruent with generational habitus.…”
Section: Discussionsupporting
confidence: 82%
“…Studies of SWB have also examined its association with environmental factors, with an emphasis on the importance of the geographically proximal environment for older adults, particularly those who are retired or becoming frail and therefore likely to be spending more time in their immediate neighborhood (8). Several studies showed that certain physical attributes of the neighborhood, such as quality public transportation (9) and access to green/ recreational areas (10,11), were positively associated with higher levels of SWB.…”
Section: Introductionmentioning
confidence: 99%
“…Social exclusion is seen to be a process; a process which is largely considered to be related to societal systems and/or agencies-such as labour market, transport, legal system [25,30,31,34,35,47,48]. The processes are dynamic in nature and interact with each other [16,26,28,34]. As a result, individuals face deprivation in multiple dimensions including poverty at a particular point in time-as an intermediate outcome [33,38,46].…”
Section: Criteria For the Review Of Transport Disadvantage Measuresmentioning
confidence: 99%